Comparisons of Vitreal Angiogenic, Inflammatory, Profibrotic Cytokines, and Chemokines Profile between Patients with Epiretinal Membrane and Macular Hole - Lu Chen; Weiwei Zhang; Ping Xie; Jiangdong Ji; Huiming Qian; Songtao Yuan; Qinghuai Liu; Zizhong Hu (Journal of Ophthalmology)
Objectives. Idiopathic epiretinal membrane (iERM) or idiopathic macular hole (iMH) is frequently used as a “healthy” control in comparison of vitreous cytokines with other vitreoretinal diseases. This study aimed to investigate if there is a difference in vitreal cytokines expression between patients with iERM and iMH. Methods. In this prospective study, all subjects received standard pars plana vitrectomy surgery, and 0.5 ml of native vitreous sample was extracted during the vitrectomy. Luminex technology and enzyme-linked immunosorbent assay were used to profile the concentration of 52 classic angiogenic, inflammatory, and profibrotic cytokines and chemokines. Statistical analyses were performed by the Mann–Whitney U test, followed by multiple comparisons by the Bonferroni correction. Results. Vitreal samples from 13 iERM and 24 iMH were studied. Of the 52 tested cytokines, 41 were similar in expression, and 5 were under the detection limit, while 6 cytokines (MMP-8, Eotaxin, MIP-1a, RANTES, TGF-β2, and IL-4) were differently expressed between two groups (p<0.05). Nevertheless, these significances disappeared after the adjustment of Bonferroni correction. Conclusion. The tested cytokines showed similar expression between iERM and iMH patients. This indicates that eyes with iERM or iMH can be together served as “healthy” controls.